Princess on the brink / Meg Cabot - Cabot, Meg
Princess Mia's junior year in high school begins with a difficult course load, a crazy student council race, Grandmere's search for temporary lodging, and learning that her boyfriend is moving to Japan for a year, partly because she will not sleep with him.